(untitled) (Prilozi za orijentalnu filologiju, 2017)
This study describes a mosque in Mostar, used primarily by members of the tanning craft. The mosque was built in late 16th or early 17th century. It was built by Hajji Kurt, the ancestor of the Mostar family of Kurts, which can be derived from a provision in his will. Today, this building is listed as a cultural monument. The said will is annexed to this paper.